3.0 T multi-parametric MRI reveals metabolic and microstructural abnormalities in the posterior visual pathways in patients with thyroid eye disease - Luo, Lan; Zhang, Liling; Huang, Huaidong; Guan, Jitian; Zhang, Xiaolei; Lin, Yan; Wu, Renhua (Frontiers in Neuroscience, 2024)
We aim to explore the microstructural and metabolic changes in visual pathways in patients with thyroid eye disease (TED) using 3T multi-parametric MRI. Thirty-four TED patients (inactive group=20; active group=14; acute group=18; chronic group=16) and 12 healthy controls (HC) were recruited from November 2020 to July 2021. Proton magnetic resonance spectroscopy ( 1 H-MRS), glutamate chemical exchange saturation transfer (GluCEST) and diffusion kurtosis imaging (DKI) were performed on 3.0T MR scanner. Data analysis and group comparisons were performed after MR data processing. As compare to HC group, the levels of total choline (tCh) in optic radiation (OR) in active group ([1.404 ± 0.560] vs. [1.022 ± 0.260] ; p < 0.05) . Glutamine(Gln) levels were higher in OR in the chronic group than those in HCs and were positively correlated with the levels of thyroglobulin antibody (TgAb), thyroid peroxidase antibody (TPOAb), free triiodothyronine (FT3) and FT4 in chronic group. Glutamate(Glu) levels by 1 H-MRS did not show significant differences between any two groups. Interestingly, MTRasym(3.0 ppm)GluCEST effect was higher in OL in inactive group, active group, acute group and chronic group than those in HCs, and was positively correlated with glutamate Glu levels in OL in 1 H-MRS. Fractional anisotropy (FA) values from DKI in OR in acute group were significantly lower than those in HCs. Our initial study demonstrate that GluCEST performs better than 1 H-MRS to monitor Glu glutamate alterations in visual pathway in TED patients.Changes of brain glutamine levels in TED patients are closely related to their associated hormones alterations, indicating that disease injury status could be reflected through non-invasive metabolites detection by brain 1 H-MRS. FA is the most sensitive DKI index to reveal the visual pathway impairment in TED patients. Altogether, our study revealed that 3T multiparametric MR techniques are useful to demonstrate metabolic and microstructural alterations in visual pathways in TED patients. We found that damage to visual pathways occurs in mild TED cases, which not only offers a new approach to the diagnosis of dysthyroid optic neuropathy, but it also demonstrates neuropathy in TED is a gradual and continuous spatio-emporal progression.